Anatomical Study of Posterior Clinoid Process (PCP) and Its Clinical Meanings. Issue 2 (March 2015) - Cheng, Ye; Chen, Yong; Zhou, Zijian; Zhu, Jiajing; Feng, Yan; Zhao, Gang
<x xml:space="preserve">Abstract</x> Purpose The aim of this study is to provide a new and comprehensive anatomic study of the posterior clinoid process (PCP) as well as data for PCP location to guide the surgeons in endoscopic surgery. Materials and Methods Computed tomography angiography images of 120 PCPs and structures around them in adults were reviewed. The measurement was on coronal, sagittal, and axial planes after multiplanar reconstruction. The length, width, and thickness were accessed for the best understanding of the feature of PCP. The distance from the base of the PCP and the middle lowest point of the sellar floor was measured to find the position of the PCP during the transphenoid approach. Result PCP varies in width and thickness in different portions of it and is closely related to the internal carotid artery and posterior communicating artery, which makes it an important landmark during surgery. Conclusion The shape of PCP is various, and the analysis of its relationship to the important structures around it is of great value. In addition, the preoperative radiological evaluation plays a major role in patients considered for endoscopic sinus surgery. Detailed preoperative analysis of the anatomy of the sphenoid sinus and its boundaries is crucial in facilitating entry to the pituitary fossa and reducing intraoperative complications.